ミズホ カンソク キョテン フキン ノ セッピョウガク テキ ジョウタイ ニツイテ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 渡辺, 興亜; ワタナベ, オキツグ; 吉村, 愛一郎; ヨシムラ, アイイチロウ; WATANABE, Okitsugu; YOSHIMURA, Aiichiro (国立極地研究所, 1972)
P(論文) The Mizuho Camp, located at lat. 70°42.1'S and long. 44°17.5'E, about 300km southeast of Syowa Station, was established by JARE 11 (1970-71) wintering party in the winter of 1970 as an observatory of scientific researches on the inland area. During the 22 days trip the party made glaciological observations of the winter surface of inland ice. After the trip the observatory hut was constructed to install the instruments for long-term meteorological observations. A four-meter deep snow pit was dug and boring down to a depth of 20m was performed for snow stratigraphic study of surface snow layer, and observation zones for long-term observations were settled. By means of these facilities and other field observations carried out in the vicinity of the Mizuho Camp, the following researches were made : 1. Survey of ice sheet topography near the Mizuho Camp and observations of surface reliefs. 2. Observations of occurrence of glazed surface and its distribution. 3. Observations of surface snow cover in the wall of the 4m deep snow pit and with the boring core from the depth of 4m down to 20m. Measurements of the snow temperature from the surface down to the depth of 10m. The results of these observations are as follows. Mean air temperature estimated from the snow temperature at the depth of 10m is -32.2℃. Annual snow accumulations are in the range from 140mm to 150mm in water. However, it is possible that these values would be considerably reduced if some years of no deposition are taken into account. departmental bulletin paper